A method for efficient parallel computation of Tate pairing. (2nd March 2012) - Su, Zhitu; Sun, Chunhui; Li, Hui; Ma, Jianfeng
The calculation of pairing plays a key role in pairing-based cryptography. Usually, the calculation is based on Miller's algorithm. However, most of the optimisations of Miller's algorithm are of serial structure. In this paper, we propose a method to parallel compute Tate pairing efficiently. We split the divisor in Miller's algorithm into three parts. Then we use efficiently computation endomorphism and precomputation method to reduce computational cost. Compared with general version of Miller's algorithm in serial structure, our method has a gain of around 50.0%.